The effect of drying conditions using a food dehydrator on the physical and chemical characteristics of red cayenne pepper powder (Capsicum frutescent L.) - Lourenza, Sintikhe; Murdianto, Wiwit (Journal of Tropical AgriFood, 2026)
Red cayenne pepper (Capsicum frutescens L.) is an important horticultural commodity in Indonesia with high demand; however, its high moisture content makes it highly perishable. One way to extend its shelf life is to process it into powder through drying. Drying using a food dehydrator is considered more effective because it allows precise control of temperature and time, which affects the final product quality, including moisture content, color, and vitamin C, β-carotene, and capsaicin levels. This study aimed to determine the effects of different drying temperatures and durations using a food dehydrator on the physicochemical characteristics of red cayenne pepper powder. A Completely Randomized Factorial Design was used with two factors: drying temperature (50, 60, and 70°C) and drying time (16, 20, and 24 h), resulting in nine treatment combinations with three replicates. The parameters observed included moisture content, yield, color (L*, a*, and b*), vitamin C, β-carotene, and capsaicin content. The results showed that increasing temperature and drying time significantly decreased the moisture content, yield, and vitamin C content, while increasing the brightness and redness of the pepper powder. β-carotene content increased at moderate temperatures and decreased at higher temperatures, while the highest capsaicin content was found at 60 °C for 20 h (998.96 ppm or 16,083.33 SHU) and decreased at 70 °C. Overall, drying at 60 °C for 20 h produced red cayenne pepper powder with optimal physicochemical quality.